APLIKASI KOMPOS SERASAH DAUN KARET DAN PUPUK NPK TERHADAP PERTUMBUHAN BIBIT KARET (Hevea brasiliensis Muell Arg.) PADA MEDIA GAMBUT - Rahman, Krisma; Fitry Ramanda, Rika; Sopiana, Sopiana (Politeknik Negeri Ketapang, 2024)
Rubber leaf litter has the potential to become compost as a new alternative. The aim of the study was to determine the growth of rubber seedlings on the application of rubber leaf litter compost and NPK fertilizer in peat soil media, and to determine the interaction between the application of rubber leaf litter compost and NPK fertilizer. The research was carried out from April to July 2022 at the Ketapang State Polytechnic Experimental Garden. This study used a factorial Completely Randomized Design (CRD) with a combination of 16 treatments and 3 replications. The first factor is rubber leaf litter compost (K) consisting of K0 (without rubber leaf litter compost), K1 (rubber leaf litter compost 250 g/polybag), K2 (rubber leaf litter compost 350 g/polybag) and K3 (rubber leaf litter compost). 450 g/polybag) and the second factor of NPK fertilizer (M) consisted of M0 (without NPK), M1 (NPK 1.25 g/polybag), M2 (NPK 2.5 g/polybag) and M3 (NPK 3.75 g /polybag). The data obtained were analyzed statistically by Analysis of Variance (ANOVA). If it is significantly different, then the Duncan Multiple Range Test (DMRT) will be further tested at the 5% level. The results showed that the application of rubber leaf litter compost and NPK fertilizer on peat soil media had a significant effect on seedling height, number of umbrellas, root length, seedling wet weight and seedling dry weight. Compost of rubber leaf litter 450 g/polybag and NPK fertilizer 3.75 g/polybag is the best dose to increase the growth of rubber plant seeds in peat soil media with seedling height of 66.53 cm, number of umbrellas 7.30 strands, root length 66.13 cm, seedling wet weight 50.76 g and seed dry weight 28.23 g.